Climate resilience programmes and technical efficiency: evidence from the smallholder dairy farmers in the Brazilian semi-arid region. (16th March 2022) - Gori Maia, Alexandre; Silveira, Rodrigo Lanna Franco da; Veneo Campos Fonseca, Camila; Burney, Jennifer; Cesano, Daniele
ABSTRACT: This paper evaluates the technical efficiency of smallholder dairy farmers assisted by a climate resilience programme in the Brazilian semi-arid region. We use stochastic frontier models applied to a panel with quarterly data for 43 dairy family farmers assisted by the MAIS programme ( Módulo Agroclimático Inteligente e Sustentável ) between January 2016 and March 2018. Results highlight how the assistance to implement climate-smart production practices, in addition to access to basic technologies, played a key role in improving the frontier of production of dairy farmers. We also show that increasing temperature continues to be the main threat to the continuous growth of technical efficiency in the region. Our findings provide insights for policy and decision-makers in designing adaptive strategies to reduce the vulnerability of impoverished family farmers that face extreme weather events.